Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures